2010
DOI: 10.1007/s10571-010-9609-6
|View full text |Cite
|
Sign up to set email alerts
|

Detoxified Extract of Rhus verniciflua Stokes Inhibits Rotenone-Induced Apoptosis in Human Dopaminergic Cells, SH-SY5Y

Abstract: Rhus verniciflua Stokes (RVS), traditionally used as a food supplement and in traditional herbal medicine for centuries in Korea, is known to possess various pharmacological properties. Environmental neurotoxins such as rotenone, a specific inhibitor of complex I provide models of Parkinson's disease (PD) both in vivo and in vitro. In this study, we investigated the neuroprotective effect of RVS against rotenone-induced toxicity in human dopaminergic cells, SH-SY5Y. Cells exposed to rotenone for 24 h-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…Choi et al (2010) reported an increased expression of TH and BDNF genes on pretreatment with T. regelii extract accounting for its neuroprotective actions. Sapkota et al (2011) reported detoxified extract of R. verniciflua prevented the downregulation of BDNF and TH against rotenone-induced toxicity. Ghaffari et al (2014) observed H. suaveolens methanol extract treatment demonstrated enhanced expression of neuronal biomarker genes BDNF and TH.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Choi et al (2010) reported an increased expression of TH and BDNF genes on pretreatment with T. regelii extract accounting for its neuroprotective actions. Sapkota et al (2011) reported detoxified extract of R. verniciflua prevented the downregulation of BDNF and TH against rotenone-induced toxicity. Ghaffari et al (2014) observed H. suaveolens methanol extract treatment demonstrated enhanced expression of neuronal biomarker genes BDNF and TH.…”
Section: Discussionmentioning
confidence: 98%
“…However, we observed the restoration of MMP by bikaverin pretreatment, which was dissipated with H 2 O 2 treatment. In their study, Sapkota et al (2011) showed the extract of R. verniciflua markedly inhibited MMP disruption, offering protection against rotenone-induced oxidative stress. Kwon et al (2012) reported E. ulmoides extract increased cell viability, inhibited cytotoxicity, and DNA condensation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17) The extract of R. verniciflua itself, as well as isolated compound, fustin have also found to attenuate neurotoxicity caused by negative insults such as rotenone and 6-hydroxydopamine. 18,19) These results suggest that R. verniciflua can act as a neuroprotectant in certain situations.…”
mentioning
confidence: 84%
“…Moreover, GDNF immunoreactivity is markedly enhanced in the substantia nigra of rats treated with Rhus verniciflua extract. Interestingly, the neuroprotective effects of Rhus verniciflua against rotenone-induced toxicity in SH-SY5Y cells include the prevention of GDNF and BDNF down-regulation in rotenone-treated cells (Sapkota et al, 2011). Ibogaine is a psychoactive compound extracted from Tabernanthe iboga, and used for decades in African folklore medicine and rituals.…”
Section: Wwwintechopencommentioning
confidence: 99%